2006
DOI: 10.1017/s0263034606060757
|View full text |Cite
|
Sign up to set email alerts
|

Status of the development of ignition capsules in the U.S. effort to achieve thermonuclear ignition on the national ignition facility

Abstract: An important component of the U.S. effort to achieve thermonuclear ignition in 2010 on the National Ignition Facility is the development of high quality 2 mm diameter spherical capsules to function as the ablator and contain the cryogenic DT fuel. Three ignition capsule designs have been developed, and detailed fabrication specifications for each design have been established and placed under change control. A research program with activities coordinated mainly between Lawrence Livermore, General Atomics and Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It is proposed to use the method of a dynamic plasma phase plate (Voronich et al, 2001) for smoothing spatial intensity distribution of heating radiation on the target. The optical transparency of a plasma layer is an essential method of a dynamic plasma phase plate, which leads to the necessity of using the low density volume-structured media (Borisenko et al, 1994(Borisenko et al, , 2008Khalenkov et al, 2006;Moreau et al, 2009;Yu et al, 2009b) Volume-structured materials are considered as different functional elements in the inertial confinement fusion (ICF) targets (Dunne et al, 1995;Gus'kov & Rosanov, 1997;Bugrov et al, 1997Bugrov et al, , 1999aBugrov et al, , 1999bNazarov et al, 1999;Cook et al, 2008;Nobile et al, 2006). First of all, smoothing of a heating inhomogeneity and production of a steady compression of the ICF targets prove to be possible applications of those materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed to use the method of a dynamic plasma phase plate (Voronich et al, 2001) for smoothing spatial intensity distribution of heating radiation on the target. The optical transparency of a plasma layer is an essential method of a dynamic plasma phase plate, which leads to the necessity of using the low density volume-structured media (Borisenko et al, 1994(Borisenko et al, , 2008Khalenkov et al, 2006;Moreau et al, 2009;Yu et al, 2009b) Volume-structured materials are considered as different functional elements in the inertial confinement fusion (ICF) targets (Dunne et al, 1995;Gus'kov & Rosanov, 1997;Bugrov et al, 1997Bugrov et al, , 1999aBugrov et al, , 1999bNazarov et al, 1999;Cook et al, 2008;Nobile et al, 2006). First of all, smoothing of a heating inhomogeneity and production of a steady compression of the ICF targets prove to be possible applications of those materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, laser laboratories worldwide are participating in the effort to understand the details of beam matter interaction physics necessary to achieve the conditions of inertial fusion (Laska et al, 2006;Lontano et al, 2006;Borghesi et al, 2005;Schaumann et al, 2005). The scientific discussion for many years shows (Meyer-ter-Vehn et al, 1990;Funk et al, 1998) and it was confirmed here that the target design is a most crucial issue for the experimental facilities as well as for a future full scale driver (Nobile et al, 2006; …”
mentioning
confidence: 52%
“…A prism-raster focusing system provided large enough (7 Â 7 mm 2 ) square irradiation spot on a target with uniform intensity distribution to ensure initially planar SW generation. The moderate laser intensities q ¼ 0.1-1 GW/cm 2 and long pulse duration of 100 ns has distinguished our experiments from those performed at the ICF-scale huge powerful lasers with high intensities q ¼ 1-100 TW/cm 2 and nanosecond pulses (see, i.e., Kilkenny et al, 1994Kilkenny et al, , 2005Farley et al, 1999;Nobile et al, 2006;Aglitskiy et al, 2006).…”
Section: Liquid-filled Laser-driven Shock Tube Conceptmentioning
confidence: 91%